Positive Education Interventions Prevent Depression in Chinese Adolescents - Zhao, Yukun; Yu, Feng; Wu, Yiwen; Zeng, Guang; Peng, Kaiping (Frontiers in Psychology, 2019)
Positive education aims to improve students’ academic performance as well as their well-being and character strengths. In contrast to traditional school counseling methods, which are typically post hoc and pathological, positive education advocates a preventive and positive approach, which teaches students well-being skills that can reduce the chances of depression before it occurs. The current study tested this hypothesis by using a pseudo-experiment design. Six 8th grade classes (N = 173) in a Chinese school were randomly assigned into two groups. In the experiment group, students took positive education courses once a week that taught them primarily knowledge and skills related to positive emotions. Students in the control group took regular moral education courses. After one semester, the level of depression of students in the experiment group had no significant change while that of students in the control group increased significantly. The results showed that adolescent depression can be prevented by positive emotion interventions. Implications and limitations are discussed.